2019
DOI: 10.1038/s41467-019-08733-w
|View full text |Cite
|
Sign up to set email alerts
|

Phenazine production promotes antibiotic tolerance and metabolic heterogeneity in Pseudomonas aeruginosa biofilms

Abstract: Antibiotic efficacy can be antagonized by bioactive metabolites and other drugs present at infection sites. Pseudomonas aeruginosa, a common cause of biofilm-based infections, releases metabolites called phenazines that accept electrons to support cellular redox balancing. Here, we find that phenazines promote tolerance to clinically relevant antibiotics, such as ciprofloxacin, in P. aeruginosa biofilms and that this effect depends on the carbon source provided for growth. We couple stable isotope labeling wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
187
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(209 citation statements)
references
References 55 publications
10
187
2
1
Order By: Relevance
“…S5B), which are not substrates for the efflux pumps upregulated by PYO 11 . This finding contrasts with the conclusions of two previous studies on phenazine-mediated antibiotic tolerance, which claimed that phenazines broadly increase tolerance to all classes of antibiotics except cationic peptides 9,10 . However, one study focused on colony biofilms that produced only phenazine-1-carboxylic acid and phenazine-1-carboxamide 9 , which are less toxic than PYO 8 and consequently may induce a different set of cellular responses.…”
Section: Responses To the Self-produced Natural Antibiotic Pyocyanin contrasting
confidence: 99%
See 1 more Smart Citation
“…S5B), which are not substrates for the efflux pumps upregulated by PYO 11 . This finding contrasts with the conclusions of two previous studies on phenazine-mediated antibiotic tolerance, which claimed that phenazines broadly increase tolerance to all classes of antibiotics except cationic peptides 9,10 . However, one study focused on colony biofilms that produced only phenazine-1-carboxylic acid and phenazine-1-carboxamide 9 , which are less toxic than PYO 8 and consequently may induce a different set of cellular responses.…”
Section: Responses To the Self-produced Natural Antibiotic Pyocyanin contrasting
confidence: 99%
“…P. aeruginosa produces several redox-active, heterocyclic compounds known as phenazines 7 . Despite possessing broad-spectrum antimicrobial activity 7 , including against P. aeruginosa itself 8 , phenazines have recently been shown to promote tolerance to clinical antibiotics under some circumstances, via mechanisms that have yet to be characterized 9,10 . Here, we sought to assess potential broader implications of the phenomenon by investigating whether phenazine-mediated tolerance to clinical antibiotics in P. aeruginosa is driven by cellular defenses that evolved to mitigate self-induced toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…While this article was in preparation, a study was published that demonstrated this effect. When P aeruginosa biofilms are studied with GFP, only a single metabolically active layer appears; however, using a new method based on stable isotope labeling, Schiessl et al showed a second activity layer in the zero DO area, even in the absence of nitrate . This layer was present below an intermediate low‐activity adaptation area, as shown in our AnaeroTrans experiments.…”
Section: Discussionmentioning
confidence: 91%
“…Phenazines are colorful redox-active molecules that are produced by numerous microbial species including the bacterium, Pseudomonas aeruginosa (Turner and Messenger, 1986). P. aeruginosa strains are ubiquitous yet perhaps most well-known for their roles in chronic infections where their growth as biofilms renders them antibiotic tolerant and contributes to patient morbidity and mortality (Costerton et al, 1999); importantly, phenazines support the development of anoxic, antibiotic tolerant biofilm regions (Dietrich et al, 2013a;Jo et al, 2017;Schiessl et al, 2019). While significant progress has been made in defining the composition of the P. aeruginosa biofilm matrix (Colvin et al, 2012) and mapping the zones of phenazine production within it (Bellin et al, 2014(Bellin et al, , 2016, we still have much to learn about how phenazines facilitate EET within the matrix.…”
Section: Introductionmentioning
confidence: 99%